2021
DOI: 10.1111/ans.17299
|View full text |Cite
|
Sign up to set email alerts
|

The factors associated with obliteration following stereotactic radiosurgery in patients with brain arteriovenous malformations: a meta‐analysis

Abstract: Background: Various factors have been reported to affect the obliteration of brain arteriovenous malformations (AVM) following stereotactic radiosurgery (SRS). This meta-analysis was conducted to identify the factors potentially associated with AVM obliteration after SRS. Methods: We comprehensively searched databases and included studies that evaluated predictors of AVM obliteration after SRS using Cox proportional hazard regression analysis. Hazard ratios (HRs) with 95% confidence intervals (CIs) were utiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…This approach reduces the need for frequent invasive angiographic procedures during follow-up. Furthermore, the significance of peri-nidal T2 hyperintensity in predicting AVM obliteration after SRS adds another layer to post-treatment assessment [67,68]. Collectively, these findings underscore the importance of a combined imaging approach, incorporating PASL and ASL in MRI, for a comprehensive and effective post-treatment follow-up in AVM management [69,70].…”
Section: Post-treatment Follow-up Of Avmsmentioning
confidence: 93%
See 1 more Smart Citation
“…This approach reduces the need for frequent invasive angiographic procedures during follow-up. Furthermore, the significance of peri-nidal T2 hyperintensity in predicting AVM obliteration after SRS adds another layer to post-treatment assessment [67,68]. Collectively, these findings underscore the importance of a combined imaging approach, incorporating PASL and ASL in MRI, for a comprehensive and effective post-treatment follow-up in AVM management [69,70].…”
Section: Post-treatment Follow-up Of Avmsmentioning
confidence: 93%
“…In this context, the need for recurrent radiological follow-ups over several years advocates for noninvasive techniques. AVM volume and radiation dose are the most significant factors that impact the obliteration after SRS [67]. In a retrospective series published by Kodera et al, including seven patients, ASL demonstrated a correlation with DSA in detecting residual persistent AVM shunts [68].…”
Section: Detection Of Residual Avms Following Srsmentioning
confidence: 98%